2002
DOI: 10.1093/oxfordjournals.schbul.a006942
|View full text |Cite
|
Sign up to set email alerts
|

Proton Magnetic Resonance Spectroscopy (1H MRS) in Schizophrenia: Investigation of the Right and Left Hippocampus, Thalamus, and Prefrontal Cortex

Abstract: Single voxel proton magnetic resonance spectroscopy (1H MRS) was used to study the metabolites N-acetylaspartate (NAA), choline (CHO), and myo-inositol (ml) in order to test a neurodegenerative hypothesis in schizophrenia (decrease of NAA, increase of CHO, and increase of ml) and a cerebral asymmetry of these metabolites. 1H MRS was performed in 17 schizophrenia patients and 14 healthy subjects in three cerebral areas highly involved in the pathophysiology of schizophrenia (the prefrontal cortex, the thalamus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 57 publications
1
19
1
Order By: Relevance
“…This result is incompatible with a neurodegenerative hypothesis of 17 schizophrenia [28] but may indicate either decreased glial content or more dysfunctional glia in more severe disease [30].…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…This result is incompatible with a neurodegenerative hypothesis of 17 schizophrenia [28] but may indicate either decreased glial content or more dysfunctional glia in more severe disease [30].…”
Section: Discussioncontrasting
confidence: 63%
“…With respect to schizophrenia, an increase in mI concentrations compared to healthy controls would be compatible with the neurodegenerative hypothesis but has not been found as of yet [28]. Instead, most studies have shown that mI levels in schizophrenia are largely unaltered (as reviewed in [29]).…”
Section: Introductionmentioning
confidence: 95%
“…The regionally lower levels of GCPII expression we demonstrated in schizophrenia are not likely due to atrophy within the frontal or mesial temporal lobe since schizophrenia is not likely a neurodegenerative disease -the composition of neurons and glia remain largely intact (Lim et al, 1998), particularly in dorsolateral PFC (Molina et al, 2006), although there is a demonstrable decrease in hippocampal volume that is diagnostically specific (Harrison, 2004). However, some MRS-based studies posit that regionally low NAA levels may indeed be due to neuron loss or at least dysfunction (Delamillieure et al, 2002).…”
Section: 1mentioning
confidence: 69%
“…40 There is evidence suggesting that alterations in brain mI may be associated with psychiatric disorders such as bipolar disorder and schizophrenia, 90 but most spectroscopy studies have reported normal mI concentrations in several brain regions in schizophrenic patients. 18,28,91,92 Hence, the verdict on mI abnormalities in schizophrenia awaits further study.…”
Section: Discussionmentioning
confidence: 99%